Komunikasi Interpersonal dalam Keluarga Broken Home di Desa Lembang - Denisa Nuraini; Taufiq Furqon Nurhakim (Jurnal Ilmiah Teknik Informatika dan Komunikasi, 2025)
Interpersonal communication is a fundamental aspect in maintaining harmonious relationships between family members. In broken home families, the communication process often experiences obstacles due to division, conflict, or the absence of one of the parental figures, which has an impact on the psychological condition of the child and the dynamics of family relationships. This phenomenon is important to study in order to understand how communication can continue amidst these limitations. This study aims to determine the form of interpersonal communication that occurs in broken home families, especially in terms of six main aspects: openness, empathy, support, positive feelings, equality, and similarity. This study uses a qualitative approach with a descriptive study method. Data collection techniques were carried out through in-depth interviews with three informants from broken home families in Lembang Village, West Bandung Regency. The results of the study showed that interpersonal communication in broken home families tends not to run optimally. Most informants have difficulty in building open and equal communication. Even so, there are efforts from each individual to maintain relationships through aspects of empathy and emotional support, although in a limited form. In conclusion, interpersonal communication in broken home families is greatly influenced by emotional conditions, parenting patterns, and closeness between family members. Even though it is not completely harmonious, some aspects of communication can still be formed, especially if there is a willingness from the parties involved to understand and support each other.